Pressing crowd noise impairs the ability of anxious basketball referees to discriminate fouls - Sors, F.; Tomé Lourido, D.; Parisi, V.; Santoro, I.; Galmonte, A.; Agostini, T.; Murgia, M. (Frontiers in Psychology, 2019)
The decision-making processes of referees in sports are affected by many factors, including the pressure of spectators. While the home/visitor bias has been previously investigated, the role of crowd noise has been less studied. In the present study, we investigated how the crowd noise (calm vs. pressing) influence the decisions of basketball referees, when examining videos of potential fouls. In doing so, we also considered the level of competitive anxiety of referees (low vs. high anxiety), as factor potentially interacting with the pressure exerted by the spectators. A 2 × 2 ANOVA (Crowd noise x Anxiety) revealed a significant interaction [F(1,28) = 7.33; p < 0.05; ?2p = 0.21; power = 0.74], with the highly anxious referees showing poorer performances in the pressing crowd condition [t(14) = 2.24; p < 0.05; d = 0.64]. The results indicate that the crowd noise does not seem to affect the referees' decisions, unless we consider the anxiety. The present findings suggest that the decisions of referees with high anxiety might be more easily influenced by external factors like crowd noise. Based on these results, referees' federations should consider the possibility to develop training protocols dedicated to highly anxious referees, to avoid their decisions from being biased by spectators' pressure.